The diversity, lexicon and cultural practices of family medicinal plants by Tetun Tribe in Malaka, East Nusa Tenggara, Indonesia - HESTIYANA HESTIYANA; MAXIMUS M. TAEK; RIANI RIANI; JAHDIAH JAHDIAH; RISSARI YAYUK (Society for Indonesian Biodiversity, 2023)
Abstract. Hestiyana, Taek MM, Riani, Jahdiah, Yayuk R. 2023. The diversity, lexicon and cultural practices of family medicinal plants by Tetun Tribe in Malaka, East Nusa Tenggara, Indonesia. Biodiversitas 24: 5359-5367. Medicinal plants are part of traditional culture used by humans to cure illness and improve health. The knowledge, perception and tradition of medicinal plants are unique to certain ethnic groups and therefore imbedded in the local language and passed down for generations. This study aims to describe the diversity and lexicon of family medicinal plants (TOGA) and its cultural practices by Tetun ethnic in Malaka District, East Nusa Tenggara Province, Indonesia. This study used a qualitative descriptive method with an ethnolinguistic approach and combined primary and secondary data. Primary data was collected by documenting a list of lexicons of medicinal plants in TOGA by the Tetun ethnic obtained from traditional healers, old people and community leaders through a series of interviews in the field. Secondary data was obtained from published sources related to this theme of research. The results of the study show that there are 32 lexicons of medicinal plants used by Tetun Tribe. These lexicons can be classified as basic words or monomorphemics (20 plants) and phrases (12 plants). Medicinal plant parts used include roots, rhizomes, tubers, stems, bark, leaves, flowers, fruits and seeds. Methods of preparation of medicinal plants are by boiling, grinding, then rubbing on the affected body part, chewing and brewing with hot water. The Tetun’s knowledge of health benefits of medicinal plants is in line with scientific evidences.